Habitualization of Satlogi Santri Value as Core Value in Building Moderate Islamic Education - Fauzi, Ahmad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The habitualization of local wisdom values (satlogi santri) is essentially inseparable from the ideas and thoughts of kiai on their understanding and interpretation of the Qur'an, and al-Hadith, as well as dialoguing with social realities in the community, both internal and external to the pesantren, thus the relationship then gives birth to a new culture which is then known as satlogi santri. The existence of local wisdom values is continuously maintained and transmitted in pesantren institutions, until finally it becomes part of the pesantren tradition and is used as social capital, thus the habitualization of local wisdom values above is then used as a core value in building moderate Islamic education, so that it can then influence the thinking and social behavior of individuals who can ultimately give birth to character, or attitudes of tawasuth, tawazun, tasāmuh, tahadhdhur, musawah, i'tidal, al-Islah, tathawur wa Ibtikar and shura, in accordance with the noble values of pesantren (tend to religious and moral values).